Oral Midazolam Premedication for Children Undergoing General Anaesthesia for Dental Care - Saad A. Sheta; Maha AlSarheed (International Journal of Pediatrics)
Objectives. To assess the efficacy and safety of injectable midazolam administered orally in 3 different doses in children undergoing complete dental rehabilitation under GA. Subjects and Methods. 60 children aged 2–6 years were enrolled in the study. The children were randomly assigned to one of 3 groups and received orally 0.5, 0.75, or 1.0 mg/kg of injectable midazolam mixed with apple juice 30 minutes before separation from parents. The following measurements were assessed: patient's acceptance of the medication, reaction to separation from parents, sedation scores, and recovery conditions. Results. More children were comfortable with parent separation in the group that received the 1.0 mg/kg dose (90%) compared to the group that received the 0.75 mg/kg dose (75%) and the group that received the 0.5 mg/kg dose (55%). The number of children who had desirable sedation was similar in the 0.75 mg/kg and 1.0 mg/kg dose groups. Twenty five percent of the children in the group that received the 0.5 mg/kg dose did not allow venepuncture before induction of GA, and induction of GA was poor for 20% of the children in this group. An increasing number of children scored excellent in terms of ease of venepuncture in 0.75 mg/kg dose group (10%) and in the 1.0 mg/kg dose group (20%) and in terms of induction of GA, 25% and 35%, respectively. Recovery of spontaneous ventilation and extubation was delayed by over 15 minutes in 2 children in the 1.0 mg/kg dose group. Conclusion. The dose of 0.75 mg/kg of injectable midazolam given orally as premedication is acceptable, effective, and safe.